1985
DOI: 10.1530/jrf.0.0740509
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression, sialic acid, and sialyltransferase of bovine serum as a function of progesterone concentration

Abstract: Summary. Serum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…As mentioned in the previous section, the oestrogen and progesterone have previously been shown to increase sialylation in the rat and bovine models (Rajalakshmi et al 1969, Sherblom et al 1985; thus, comparisons of the serum oestrogen levels in our model indicated that the oestrogen levels were low at selection, increased at differentiation and then decreased at luteinisation (Walsh et al 2012b). This was evident in both the cow and heifer; however, the heifer exhibited approximately twofold higher serum oestrogen concentrations than the cow.…”
Section: Ff Glycan Characterisationsupporting
confidence: 61%
See 1 more Smart Citation
“…As mentioned in the previous section, the oestrogen and progesterone have previously been shown to increase sialylation in the rat and bovine models (Rajalakshmi et al 1969, Sherblom et al 1985; thus, comparisons of the serum oestrogen levels in our model indicated that the oestrogen levels were low at selection, increased at differentiation and then decreased at luteinisation (Walsh et al 2012b). This was evident in both the cow and heifer; however, the heifer exhibited approximately twofold higher serum oestrogen concentrations than the cow.…”
Section: Ff Glycan Characterisationsupporting
confidence: 61%
“…However, the analysis indicated a higher proportion of nonsialylated glycans and a corresponding decrease in sialylated glycan structures in lactating cows when compared with heifers. An increase in uterine sialic acid, which was induced by oestrogen, has been reported in the rat (Rajalakshmi et al 1969) and increases in sialic acid and sialyltransferase activity correlate with increased circulating progesterone concentrations in the bovine model (Sherblom et al 1985). The concentrations of oestrogen and progesterone are also linked with fertility in heifers and lactating dairy cows, where heifers display higher circulating progesterone concentrations and this has been linked to their higher fertility in comparison with lactating dairy cows (Crowe 2008).…”
Section: Ff Glycan Characterisationmentioning
confidence: 90%
“…Only MeSH analysis was able to uncover ST3 beta‐galactoside alpha‐2,3‐sialyltransferase 1 ( ST3GAL1 ), a gene member of the sialyltransferases family (MeSH:D012799) known to be influenced by level of progesterone in cyclic and pregnant female cattle (Sherblom et al . ).…”
Section: Resultsmentioning
confidence: 97%